Spontaneous bladder rupture of a urinary bladder with non-muscle invasive bladder cancer. (11th March 2014) - Hadjipavlou, Marios; Tharakan, Tharu; Khan, Shahid A A; Swinn, Michael
Abstract : We describe the case of a 65-year-old man who developed spontaneous bladder rupture after picking up his suitcase from a squatting position. He was known to have non-muscle invasive bladder cancer (NMIBC), managed previously with transurethral resections and intravesical chemotherapy. CT scan showed a large amount of free intraperitoneal fluid anterior to the bladder, suggestive of a urinoma. Management was initially conservative, with insertion of urethral catheter, intravenous antibiotics and fluid resuscitation. Follow-up CT scan showed resolution of the urinoma with the patient making a full recovery after 3 weeks.